Kualitas Fisik dan Kimia Silase Jerami Padi yang Dibuat Dengan Penambahan Cairan Rumen Sapi Bali - Suadnyana I M.; I G. L. O. Cakra; I W. Wirawan (Animal Science Study Program, Faculty of Animal Husbandry, Udayana University, 2019)
This study aims to determine the physical and chemical quality of rice straw silage made by the addition of Balinese cattle rumen fluid. The study was conducted in Banjar Buda Manis, Sidemen Village, Sidemen District, Karangasem Regency. Silage analysis was carried out at the Animal Nutrition and Food Laboratory, Faculty of Animal Husbandry, Udayana University. The design in the study was complete random concoction with four treatments and four replications. Treatment A (rice straw silage without rumen fluid)